Medicine, Value, and Knowledge in the Veterinary Clinic: Questions for and From Medical Anthropology and the Medical Humanities - Desmond, Jane (Frontiers in Veterinary Science, 2022)
The welcome development of the veterinary humanities, and veterinary anthropology specifically, raises the question of its potential relationship with the now well-established field(s) of the medical humanities, and of medical anthropology. Although there are national variations, the term "medical humanities" generally refers to either the tapping of the humanities to improve medical education by developing, through engagement with the humanities like literature and visual art, skills in empathy, visualization and expressivity, or alternatively, it refers to the application of humanities approaches of cultural critique to the presumptions, practices and institutions of the human medical world to denaturalize the ideologies of knowledge that contemporary human medicine professions depend upon. This article reflects on the potential impact that the development of a veterinary medical humanities could have on the field of (human) medical humanities and vice versa. Could such a development force a re-conception of notions of agency, of consent, and of the position of "patient" when the (human based) medical humanities is expanded to include both human and veterinary medicine? What would the potential usefulness, or limitations, both in conceptual and in applied terms, be of constructing a multi-species notion of "medical humanities?" What can such a comparative approach offer to veterinary medicine, in practice and in terms of the curricula of veterinary training? To reflect on these questions, this article draws on my multiple years of fieldwork in veterinary clinics and classrooms to first lay out the constituent components of the formal practice of contemporary veterinary medicine (at least in the U.S.) in terms of the roles that species specificity and relations to humans play in the delivery of care, and then seeks to center the animal in these practices to ask questions about consent, resistance, veterinary obligation, and the role of finance in comparison with human medicine. These similarities and differences will form the basis for a consideration of the effects of enlarging the medical humanities to encompass more than one species.